CORRELATION BETWEEN S100 PROTEIN EXPRESSION WITH CLINICAL STAGING NASOPHARYNGEAL CARCINOMA TYPE III - Cahyadi, Ismi; Dewi, Yussy Afriani; Aroeman, Nur Akbar (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Abstract Introduction: Nasopharyngeal carcinoma is the most found head and neck cancer, which originated from a nasopharyngeal epithelial cell, and predilection site commonly at rosen muller fossa. S100 protein inflammatory mediators are involved in the regulation of cellular processes including inflammation and malignancy. S100 protein plays a central role in the proliferation, regulation of cell apoptosis and metastasis causing continuing growth of cancer cells through activation of STAT3 by IL-6, NF-ÎºB, ROS. Objective: This study aimed to determine the correlation between S100 protein expression levels to the clinical stage of NPC WHO type III. Method: This research is a cross-sectional analytic study. This study was held in the Anatomical Pathology Department of Hasan Sadikin Hospital from August until October 2015. The study was conducted using 29 pieces of secondary data, medical records and paraffin blocks anatomical pathology of NPC patients were examined S100 protein immunohistochemistry. Result: This study was performed from 29 subjects (18 males and 9 females). There was a strong positive correlation between histoscore S100 protein expression with clinical staging p<0.05. There is a significant correlation between S100 protein expression with the clinical stage of NPC WHO type III using double regression analysis (F=15.676, p=0.000). Conclusion: There were significant correlation S100 protein expression levels to clinical stage nasopharyngeal carcinoma WHO type III.